Laparoscopic Surgery in Infants with Intra-Abdominal Cysts: Two Case Reports - Kuga, Takayuki (Society of Laparoendoscopic Surgeons, 2000)
OBJECTIVES: We report two cases of infants found to have congenital omental cystic lesion with torsion and ovarian cyst treated by laparoscopy-assisted surgery (LAS). METHODS: A laparoscope was inserted by an open method. The intra-abdominal pressure was maintained at 8 mm Hg. We diagnosed the cystic lesions with torsion. An aspirator was used to aspirate the cystic content and remove the cyst. RESULTS: No intra- or postoperative complications were encountered. Oral intake was commenced on postoperative day 2 in both patients. The cosmetic results following LAS were excellent. CONCLUSIONS: We conclude that LAS is suitable for the management of omental cystic lesions with torsion and ovarian cyst in nursing infants. An aspirator is useful in preventing spillage of cystic contents in patients with intra-abdominal cystic lesion.